Dependence of harmonic generation on primary wave pressure distribution - Baranowska, Anna (Archives of Acoustics, 2007)
The aim of this paper is theoretical analysis of harmonic generation during finite amplitudewave propagation. The paper presents mathematical model and some results of numericalcalculations. The mathematical model was built on the basis of the KZK equation. To solvethe problem the Fourier series expansion and finite-difference method were applied. The harmonicpressure amplitudes as a function of axial distance and their transverse distributions atfixed distances from the source were examined. The pressure amplitude distributions at horizontalsection were investigated, too. The calculations were carried out for different pressuredistributions on the circular source and different values of medium parameters.